2020
DOI: 10.1021/acsami.0c04093
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer of PMMA Doped with Au Nanoparticles for High-Performance Tandem Photodetectors: A Solution to Suppress Dark Current and Maintain High Photocurrent

Abstract: Currently, colloidal quantum dots (CQDs)-based photodetectors are widely investigated due to their low cost and easy integration with optoelectronic devices. The requirements for a high-performance photodetector are a low dark current and a high photocurrent. Normally, photodetectors with a low dark current also possess a low photocurrent, or photodetectors with reduced dark current possess a reduced photocurrent, resulting in low detectivity. In this paper, a solution to suppress dark current and maintain a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 41 publications
1
43
0
Order By: Relevance
“…Then, photo-generated holes transfer from CdSe/ZnS QDs to PEDOT:PSS through a matching energy band and thus leaving behind photo-generated electrons in the conduction band of the CdSe/ZnS (Figure d). The trapped electrons can also act as an additional internal electric filed for further accelerating the holes to be swept to the PEDOT:PSS channel, which is favorable for the separation of electrons and holes and thus reduces the recombination of the charge carriers and forms enhanced photocurrent compared with the dark condition (Figure c) . To support the above statement of interfacial charge transfer properties between the PEDOT:PSS channel and CdSe/ZnS QDs, the steady-state and transient-state photoluminescence (PL) spectra of CdSe/ZnS QDs and CdSe/ZnS-PEDOT:PSS hybrid structure are performed, as shown in Figure e,f.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Then, photo-generated holes transfer from CdSe/ZnS QDs to PEDOT:PSS through a matching energy band and thus leaving behind photo-generated electrons in the conduction band of the CdSe/ZnS (Figure d). The trapped electrons can also act as an additional internal electric filed for further accelerating the holes to be swept to the PEDOT:PSS channel, which is favorable for the separation of electrons and holes and thus reduces the recombination of the charge carriers and forms enhanced photocurrent compared with the dark condition (Figure c) . To support the above statement of interfacial charge transfer properties between the PEDOT:PSS channel and CdSe/ZnS QDs, the steady-state and transient-state photoluminescence (PL) spectra of CdSe/ZnS QDs and CdSe/ZnS-PEDOT:PSS hybrid structure are performed, as shown in Figure e,f.…”
Section: Resultsmentioning
confidence: 85%
“…The trapped electrons can also act as an additional internal electric filed for further accelerating the holes to be swept to the PEDOT:PSS channel, which is favorable for the separation of electrons and holes and thus reduces the recombination of the charge carriers and forms enhanced photocurrent compared with the dark condition (Figure 4c). 51 To support the above statement of interfacial charge transfer properties between the PEDOT:PSS channel and CdSe/ZnS QDs, the steady-state and transient-state photoluminescence (PL) spectra of CdSe/ZnS QDs and CdSe/ZnS-PEDOT:PSS hybrid structure are performed, as shown in Figure 4e,f. The PL intensity of the CdSe/ZnS-PEDOT:PSS hybrid film is quenched sharply compared with that of the pristine CdSe/ZnS, indicating the efficient carrier transfer and exciton dissociation at the interface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The uniform distribution of Au facilitates the transition from Au to Au‐OH ads and increases the utilization of Au; b) The presence of Fe 3 O 4 and CoFe‐LDH on the two sides of the sandwich structure regulated the electronic structure of Au, thereby improved the electrocatalytic activity of Au toward GOR; c) The presence of Au between Fe 3 O 4 and CoFe‐LDH significantly improved the intrinsic conductivity of the catalyst, which is agreed with other reported researches. [ 22b,44 ]…”
Section: Roles Of Fe3o4 and Au In Gor And Hermentioning
confidence: 99%
“…As an electrode material, Au has excellent electrical conductivity and various researches have shown that the insertion of Au between two phases can effectively improve the conductivity of electrode material. [ 22 ] Furthermore, Au is an excellent glucose oxidation catalyst as reported. [ 23 ] Therefore, inserting Au between LDH and Fe 3 O 4 may effectively improve the conductivity of the catalyst while providing catalytic activity toward GOR.…”
Section: Introductionmentioning
confidence: 96%
“…
transferring ability. [1] Recently, halide perovskites have achieved significant attention for their possessing tunable bandgap, high absorption constant in visible region, and a low-cost solution processibility for optoelectronics, [2][3][4][5][6] such as light-emitting diodes, photodetectors, and solar cells. Due to the fluctuations in hybrid methyl ammonium lead halide (MAPbX 3 ) perovskite and the instability caused by the decomposition of organic components.
…”
mentioning
confidence: 99%